Effects of a front-of-package disclosure on accuracy in assessing children's drink ingredients: two randomised controlled experiments with US caregivers of young children - Frances Fleming-Milici; Haley Gershman; Jennifer Pomeranz; Jennifer L Harris (Cambridge University Press, 2023)
Abstract Objective: Test effects of a standardised front-of-package (FOP) disclosure statement (indicating added sugar, non-nutritive sweetener (NNS) and juice content) on accuracy in assessing ingredients and perceived healthfulness of children's drinks. Design: In two randomised controlled experiments, the same participants viewed drink packages and indicated if products contained added sugar or NNS and percent juice and rated drink healthfulness. Experiment 1 (E1) included novel (non-US) children's drinks with a) product claims only (control), b) claims and disclosure, or c) disclosure only. Experiment 2 (E2) included existing children's drinks (with claims) with a) no disclosure (control) or b) disclosure. Both experiments evaluated sweetened (fruit drink and flavoured water) and unsweetened (100 % juice and juice/water blend) drinks. Potential individual differences (education level and race/ethnicity) in effects were explored. Setting: Online survey Participants: Six hundred and forty-eight US caregivers of young children (1-5 years) Results: FOP disclosures significantly increased accuracy for most ingredients and drink types, including identifying presence or absence of NNS in sweetened drinks, no added sugar in juice/water blends, and actual percent juice in fruit drinks and juice/water blends in both experiments. Disclosures also increased recognition that the novel 100 % juice and juice/water blend did not contain NNS or added sugar (E1) and existing sweetened drinks contained added sugar (E2). Disclosures reduced perceived healthfulness of sweetened drinks but did not increase unsweetened drink healthfulness ratings. Some differences by participant socio-demographic characteristics require additional research. Conclusions: FOP disclosures on children's drink packages can increase caregivers' understanding of product ingredients and aid in selecting healthier children's drinks.